Combined pulmonary vein isolation and cavotricuspid isthmus ablation shows no benefit in recurrence of atrial fibrillation. (19th May 2022) - Jacinto, S; Silva Cunha, P; Portugal, G; Valente, B; Coutinho Cruz, M; Lousinha, A; Bras, P; Delgado, AS; Bras, M; Paulo, M; Guerra, C; Teixeira, AR; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein isolation (PVI) is the mainstay of catheter ablation (CA) for atrial fibrillation (AF). Strategies have been proposed to improve the success rate of CA, such as prophylactic cavotricuspid isthmus (CTI) ablation. Despite some studies providing no, or limited, incremental benefit of CTI ablation in patients with AF, it is still frequently performed worldwide. Purpose: The aim of this study is to examine whether CTI ablation, combined with PVI, is associated with improvement in recurrence of AF, compared with PVI alone in AF patients with or without atrial flutter (AFL). Methods: We conducted a retrospective analysis of CA for AF performed at a tertiary center between September 2004 and December 2020. The procedures were divided in two groups: "PVI alone" and "PVI plus CTI ablation". Demographic, clinical, and procedure related data was retrieved. Atrial fibrillation recurrence rate at one year was analyzed for both groups and compared using logistic regression. Results: A total of 453 procedures were analyzed: PVI alone (n=378; 83.4%) and PVI with CTI ablation (n=75; 16.6%). In the PVI alone group, 12.9% of the patients had concomitant typical AFL and in the PVI plus CTI ablation, 45.8% had typical AFL. Mean age was 57.3±12.1 years, with 63.6% male patients. At one year, AF recurrence rate was higher in the combined PVI with CTI ablation group (30.4%; n=21), compared with the PVI alone group (28.4%; n=97), with no statistical difference between the two groups (Odds Ratio [OD] 1.10; 95% confidence interval [CI] 0.62-1.94; p=0.73). In the subgroup analysis, there was no difference in recurrence between patients with AF without AFL (OR: 1.9; 95% CI: 0.39-9.36; p=0.43), and in patients with AF with concomitant AFL (OR: 10.0; 95% CI: 0.9-110.3; p=0.06). Conclusion: In AF patients, irrespective of the presence of typical AFL, additional CTI ablation, compared with PVI alone, was not associated with improvement in recurrence of AF.